The Status of Women in Türkiye and Legal and Criminal Regulations for the Protection of Women - Güloğlu, Yavuz; GÜLOĞLU , Nazife Vildan (Fakultas Syariah dan Hukum, UIN Syarif Hidayatullah Jakarta, 2025)
Since the dawn of humanity, with few exceptions, almost all cultures and civilisations have exhibited a perspective that regards men as superior and women as inferior. However, in the Qur’an, Allah swears by the creation of both men and women, thereby attributing value to both. If men and women were not equally dignified as His servants, Allah would not have sworn by their creation. According to the Qur’an, the creation of women is not different from that of men; both were created from the same “nafs” (essence). The distinction between men and women lies in their abilities and roles. In Türkiye, legal and institutional mechanisms developed to combat violence against women and to protect the institution of the family are primarily addressed within the framework of Law No. 6284 on the Protection of the Family and Prevention of Violence Against Women. Crimes committed against women are regulated under the Turkish Penal Code, a general legislative instrument. Within the systematic structure of the Turkish Penal Code, the type of crime, the manner in which it is committed, its nature, and the identity of the victim are all considered in determining the basic and aggravated forms of penalties. The Code also provides for increased penalties in cases where crimes are committed against women. There are specific provisions for aggravated penalties in cases of intentional injury of women, torture and ill-treatment against women, and crimes against sexual inviolability when the victim is a woman. This study examines how the Court of Cassation, the highest court of appeal in Türkiye, interprets issues specific to criminal law—such as the element of premeditation, the concept of reasonable time, and the reduction of sentences due to unjust provocation—in crimes committed against women. The study also addresses practical problems arising from the interpretation of the law and offers solutions to issues observed in the case law of the Court of Cassation. Emphasis is placed on ensuring consistency in judicial decisions regarding crimes against women and on enhancing the predictability of the criminal justice system for individuals.